The effect of nurses’ organizational support on turnover intention: the chain-mediating role of psychological resilience and change fatigue - Liu, Zhenfan; Yan, Xiaoting; Wang, Zhitong (Frontiers in Psychology, 2025)
BackgroundNurse turnover intention remains high globally. Identifying targeted interventions to reduce turnover rates and stabilize the nursing workforce is a current priority. However, the mechanisms through which psychological resilience and change fatigue mediate the effect of organizational support on turnover intention are not fully understood.ObjectiveTo investigate the current status of nurses’ turnover intention and to explore the mediating roles of psychological resilience and change fatigue between organizational support and turnover intention.MethodsIn June 2025, 654 nurses were selected via convenience sampling. Surveys were conducted using the General Information Questionnaire, organizational support Scale, Connor–Davidson Resilience Scale (10-item), change fatigue Scale, and turnover intention Scale. A chain mediation model was constructed and validated.ResultsThe median scores (P25, P75) were as follows: turnover intention 8.00 (4.00, 10.00), organizational support 52.00 (49.00, 65.00), psychological resilience 24.00 (20.00, 30.00), and change fatigue 24.00 (20.00, 30.00). The direct effect of organizational support on turnover intention was significant (effect = −0.102). The separate mediating effects of psychological resilience and change fatigue, and their chain mediating effect, were −0.038, −0.030, and −0.010, accounting for 21.1, 16.7, and 5.6% of the total effect, respectively.ConclusionNurses’ turnover intention was at a moderately high level. The chain mediation effect of psychological resilience and change fatigue between organizational support and turnover intention was established. Management should focus on enhancing organizational support to improve psychological resilience, thereby mitigating change fatigue and ultimately reducing turnover intention, ensuring the delivery of high-quality patient care.